Designing Self-reflective and Comprehensible Visualisation for Self-care Applications - Visvalingam A.; Dhillon J.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Flow graphs; Visualization; Cognitive walkthrough; Customizability; Design Principles; Graphical representations; Heuristic evaluation; Proactive supports; Quantitative study; Suitable graphs; Health care